Patterns of coronary plaque progression: phasic versus gradual. A combined optical coherence tomography and intravascular ultrasound study. Issue 8 (December 2016) - Xie, Zulong; Hou, Jingbo; Yu, Huai; Jia, Haibo; Du, Hongwei; Lee, Hang; Yu, Bo; Tian, Jinwei; Jang, Ik-Kyung
Abstract : Objective: Some plaques grow slowly in a linear manner, whereas others undergo a rapid phasic progression. However, the detailed in-vivo relationship between plaque characteristics and plaque progression pattern has not been reported. The current study aimed to investigate the plaque progression patterns with serial intravascular ultrasound (IVUS) examinations, and to correlate baseline plaque characteristics assessed by optical coherence tomography and IVUS with plaque progression patterns. Methods: A total of 248 coronary lesions from 157 patients were identified and imaged by both optical coherence tomography and IVUS at baseline. IVUS examination was repeated at 6 and 12 months. Plaque progression was defined as greater than or equal to 5% increase in percent atheroma volume by IVUS. The progression patterns were divided into three groups: no progression, rapid phasic progression, and gradual progression. Results: Among 248 lesions, 190 (77%) showed no progression. Among 58 lesions with progression, 20 (34%) showed gradual progression, whereas 38 (66%) showed rapid phasic progression. Multivariate analysis indicated that thin-cap fibroatheroma [odds ratio (OR)=5.24, 95% confidence interval (CI) 2.04–13.4; P =0.001], microvessel (OR=2.20, 95% CI 1.10–4.79; P =0.045), and positive remodeling (OR=2.64, 95% CI 1.19–5.81; P =0.016) were associated independently with rapid phasic progression. Conclusion: Three-quarters of coronary plaques did not progress over time with contemporary medical treatment. Among the lesions with progression, one-third showed a gradual pattern and two-thirds showed a rapid phasic pattern. The presence of thin-cap fibroatheroma, microvessel, and positive remodeling were the independent predictors for rapid phasic pattern progression of coronary atherosclerotic plaques. Abstract : Supplemental Digital Content is available in the text.